Prevalence of low back pain and disability among secondary school teacher in the eastern province of the Kingdom of Saudi Arabia: a cross-sectional analytical study - Almansour, Abdulelah H.; Almutairi, Danah S.; Alaskar, Turki M.; Kalkatawi, Mohannad S.; Aljubair, Mohammed F.; Alotaibi, Rakan S.; AlHarkan, Khalid S.; Alqahtani, Hatem A.; AlOmar, Reem S. (Frontiers in Public Health, 2024)
Introduction Lower back pain is common worldwide and affects over 600,000 people annually, including teachers. The study aimed to investigate the prevalence of low back pain and disability among secondary school teachers in the Eastern Province of the Kingdom of Saudi Arabia. Materials and methods This cross-sectional study included secondary school teachers in the eastern province of Saudi Arabia. 34 schools were selected using a multistage stratified sampling approach. Teachers were allotted randomly and proportionally to each school. Data was collected by anonymous questionnaire having three elements: sociodemographic and health-related questions, the Standardized Nordic Questionnaire, and the Oswestry Low Back Pain Disability Questionnaire. The anthropometric data was also included. Both unadjusted and adjusted logistic regression analyses were performed. Results A total of 601 teachers participated in the study with 62.56% reported low back pain. The overall mean age was 40.31 ± 8.13 years. The male-to-female ratio was similar. Back pain was significantly higher among females than males (73.36 and 51.52%, respectively). Additionally, back pain will significantly increase when stress levels and the number of classes increases. A positive correlation was found between age with low back pain (p = 0.001).There was minimal disability in 64.63% of the 376 teachers who reported low back pain, moderate disability in 29.79%, and severe disability in 4.79%, and only three (0.8%) were considered crippled. Females were more frequently seen in moderate and crippled categories, and perceived stress levels generally increased mean disability scores. Age and female gender were revealed to be significant predictors of low back pain by logistic regression (adjusted odds ratio [OR] = 1.04, 95% confidence interval [CI] = 1.02–1.07) and (adjusted OR = 2.11, 95% CI = 1.45–3.05), respectively. The number of classes per week was also a significant predictor. Conclusion This study adds to the epidemiological evidence that reveals a high prevalence of low back pain and disability among teachers. Identified risk factors in this study may also reinforce the importance of setting different interventions and preventive measures to reduce lower back pain risk.